Interplay of noncovalent interactions in antiseptic quaternary ammonium surfactant Miramistin. Issue 4 (5th March 2019) - Dolgushin, Fedor M.; Goloveshkin, Alexander S.; Ananyev, Ivan V.; Osintseva, Svetlana V.; Torubaev, Yury V.; Krylov, Sergey S.; Golub, Alexandre S.
Abstract : Structure determination and DFT analysis of the bonding pattern in the antiseptic Miramistin were performed. Stabilization of the bent conformation of the organic cation occurs in both the crystalline and the isolated state due to noncovalent intramolecular interactions. Abstract : The molecular and crystal structure of the widely used antiseptic benzyldimethyl{3‐[(1‐oxotetradecyl)amino]propyl}ammonium chloride monohydrate (Miramistin, MR ), C26 H47 N2 O + ·Cl − ·H2 O, was determined by a single‐crystal X‐ray diffraction study and analyzed in the framework of the QTAIM (quantum theory of atoms in molecules) approach using both periodic and molecular DFT (density functional theory) calculations. The various noncovalent intermolecular interactions of different strengths were found to be realized in the hydrophilic parts of the crystal packing ( i.e. O—H…Cl, N—H…Cl, C—H…Cl, C—H…O and C—H…π). The hydrophobic parts are built up exclusively by van der Waals H…H contacts. Quantification of the interaction energies using calculated electron‐density distribution revealed that the total energy of the contacts within the hydrophilic and hydrophobic regions are comparable in value. The organicMR cation adopts the bent conformation with the head group tilted back to the long‐chain alkyl tail in both the crystalline and the isolated state due to stabilization of this geometry by several intramolecular C—H…π, C—H…N and H…H interactions. This conformation preference is hypothesized to play an important role in the interaction ofMR with biomembranes.